Your notation is really bad...
If someone is raised to the power of something else then you need to write it as 4 ^ 3 (shift and the number 6 will give you the ^ symbol).
That aside, when your asking questions try not to just copy and paste your questions in without trying or thinking about it. Rather try and word in a way which you can figure out how to do it yourself.
This is very basic arithmetics. If you have trouble with this definately speak to your teacher and hopefully they can show you how to expand and simplify algebraic expressions.
Just so this isnt spam, heres one of the answers with working
3. Simplify the following expression
(3x^2 + 2x - 3) + (5x^2 + 5)
= 3x^2 + 5x^2 +2x + 5 - 3
= 8x^2 + 2x +2
2007-02-09 15:01:43
·
answer #1
·
answered by Renesis 2
·
0⤊
0⤋
Q.1. What is the degree of this term: 5x2y3
A. Degree 5.
Degree is the exponentiation of the term. here we can see the degree of x is 2 and degree of y is 3.
as the whole term comprises x as well as y, we consider the sum of degrees of all parts as the degree of the whole term.
Q.2. what is the degree of this polynomial:
6x2y3 - 3xy2 - 2x
A. Here also, as in Q.1. we find the Degree of the first term as 3, Degree of the second term as 2, and degree of the third term as 1.
Considering the whole polynomial, the sum of degrees of all parts, ie 5, is the Degree of the whole polynomial.
Q.3. simplify the following expression:
(3x2 + 2x - 3) + (5x2 + 5)
Collect similar terms.
=> x2 terms => 3x2 + 5x2 = 8x2
=> x terms => 2x
=> integer => -3 + 5 = 2
combining all these we get,
8x2 + 2x + 2
Q.4. Simplify the following expression:
(2x2 - 5x + 10) - (x2 - 7x + 3)
A. Multiply - with the second polynomial, we get,
(2x2 - 5x + 10) + (-x2 + 7x - 3)
As in Q.3, collect similar terms.
x2 terms => 2x2 - x2 = x2
x terms => -5x + 7x = 2x
integer => 10 - 3 = 7
combing all these we get,
x2 + 2x + 7
Q.5. Multiply and simplify: 4x3(5x2-2x)
A. rewriting, => {(4x3)(5x2)} + {(4x3)(-2x)}
= 20x5 - 8x4
GOOD LUCK
MATHEMATICS REQUIRES GOOD REASONING
2007-02-09 15:09:48
·
answer #2
·
answered by natarajan@ezee 2
·
0⤊
0⤋
1. The degree of a monomial is the sum of all the exponents of the variables. x has a power of 2, y a power of 3, thus this term has degree 5.
2. The degree of a polynomial is the highest degree any of the terms have. The terms have the following degrees: 5, 3, 1. Thus, the degree of the polynomial would be 5.
3&4. When you simplify expressions by adding and subtracting, you combine terms with like variables and exponents. If it doesn't have any like terms, you don't change it. The exponents of the terms you are adding/subtracting won't be changed at all. If you are subtracting, remember that each term is getting subtracted. For 3, combine 3x^2 + 5x^2 to get 8x^2, leave 2x alone (no like terms), and combine -3 with 5 to get 2. Thus, 8x^2 + 2x + 2. For 4, you have 2x^2-x^2=x^2, -5x-(-7x)=-5x+7x=2x, 10-3=7, for x^2+2x+7
5. When you multiply things with variables, you add exponents of like variables. In this case, you must also make use of the distributive propery, which states that you must multiply each term inside the parentheses by the term outside of it. So
4x^3 ( 5x^2-2x)
= 4x^3 * 5x^2 + 4x^3 * -2x
= 20x^5 -8x^4
2007-02-09 15:02:48
·
answer #3
·
answered by Mr. Adkins 4
·
0⤊
0⤋
3. Simplify
(3x2+2x-3)+(5x2+5)
BEDMAS
brackets, exponents, division, multiplication, addition THEN subtraction
1. Work within the brackets
Bracket ONE
(3x2+2x-3)
=Multiplication
=(6+2x-3)
=Addition
=2x+6-3
=(2x+3)
Bracket TWO
(5x2+5)
=Multiplication
=(10+5)
=(15)
Now put them together
=(2x+3)+(15)
=2x+3+15
=2x+18
4. Simplify
=(2x2-5x+10)-(x2-7x+3)
=BRACKET (solve brackets first)
=MULTIPLICATION
=(4-5x+10)-(x2-7x+3)
=SUBTRACTION
=(-5x+10-4)-(x2-7x+3)
=(-5x+6)-(x2-7x+3)
For the -(x2-7x+3), you must remember that the negative AUTOMATICALLY has a one after it, so the entire bracket is supposed to be multiplied by negative one. This will change the sign from a negative to a posative
=(-5x+6)+(-x2+7x-3)
Now add them together!
=-5x+6-x2+7x-3
Group like terms
=-x2+7x-5x+6-3
Simplify
=-x2+2x+3
5. Simplify
First, do the brackets
=(5x2-2x)
Multiplication
=(10-2x)
Then the outside
=4x3
=12
Now multiply them together!
=12(10-2x)
=120-24x
They may also be looking for the simplist form of brackets such as
12(10-2x)
=(12)2(5-2x)
=24(5-2x)
2007-02-09 15:10:02
·
answer #4
·
answered by bpbjess 5
·
0⤊
0⤋
1. 5
2. 5
3. 8x2 + 2x + 2
4. x2 + 2x +7
5. 20x5 - 8x4
2007-02-09 15:02:19
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
go 2 tutor.com they can help
2007-02-09 14:53:12
·
answer #6
·
answered by aquaria374 2
·
0⤊
0⤋